KOMPETENSI PENYULUH PERTANIAN DALAM MEMBERDAYAKAN PETANI - Oos M. Anwas (LPPM Universitas Terbuka, 2011)
In line with the spirit of decentralization and national development, the demands on agricultural extension agents is focused on farmer empowerment so they can improve their quality of life independently. These efforts need to be supported by a professional agricultural extension agent. This study aimed to determine the competency of agricultural extension agents in empowering farmers. The research was conducted through a survey on government employee who work as agricultural extension agents in paddy farming area in Karawang district and in vegetable farming area in Garut district of West Java. Samples were taken randomly. The results demonstrated that the competency of agricultural extension agents were low, especially in the dimensions of entrepreneurial management, renewal management, and network system guiding. Competency dimensions in fair category were understanding the potential of the region, training management, learning management, communication management, and innovation. The t-test showed that there was no significant difference between the competency of agricultural extension agents who served in the rice agricultural area and those who served in the vegetables farming. There was also no significant difference between agricultural extension agents who continued their formal education in public universities and those who continued there formal education in private universities. The low competency of agricultural extension agents became a challenge to all parties, especially the government (central and local), education institutions, colleges that prepare extension workers and extension staff concerned.